Power assessment of lower limbs and strength asymmetry of soccer goalkeepers - František Zahálka (Acta Universitatis Palackianae Olomucensis. Gymnica, 2013)
BACKGROUND: Effective execution of vertical jump depends on the explosive power of lower limbs and their symmetrical integration mainly. Assessment of lower extremity bilateral asymmetries in soccer players is important for both injury prevention and performance. OBJECTIVE: The aim of this study was to identify and compare parameters of lower limb power in three different jump tests in elite soccer goalkeepers. The next aim was to describe and compare strength asymmetries of force exerted by lower limbs in the take-off phase in all tests. METHOD: The research group consisted of 25 elite soccer goalkeepers (age 26.5 ± 9.1 years, height 186.1 ± 7.8 cm, weight 86.7 ± 14.8 kg). Three types of a vertical jump – countermovement jump with arms included (CMJFA), countermovement jump with arms excluded (CMJ) and squat jump (SJ) were performed on two force platforms. Following parameters were assessed – maximum force during the take-off phase Fmax (N) and their relative value Frel (N • kg–1), jump height h (m) and force asymmetry between limbs (∆Fmax). RM ANOVA was used in statistical analysis. RESULTS: The type of jump had a significant effect on jump height (F2, 48 = 109.66, p < .01, η2 = .82). The highest jump was reached in CMJFA. This result was higher by 11.1% (5.01 cm) in comparison to CMJ and by 19.9% (8.98 cm) than in SJ. Type of jump significantly influenced Fmax (F1.6, 38.7 = 44.29, p < .01, η2 = .65) and Frel (F2, 48 = 50.33, p < .01, η2 = .68). Force asymmetry between limbs (∆Fmax) was significantly different with respect to the type of jump performed (F1.3, 31.7 = 5.14, p < .05, η2 = .18). The highest force asymmetry was found in CMJFA test (∆Fmax = 8.61%), while the difference in CMJ test was (7.06%) and in SJ test (∆Fmax = 3.95%). We found a significantly greater difference in ∆Fmax between CMJFA vs. SJ (p < .05) and CMJ vs. SJ (p < .01). CONCLUSION: The best results of jump height were achieved, as expected in the CMJFA but in this test also the greatest force asymmetry was detected. Monitoring of power level and strength asymmetries at the beginning of the preparatory period enables identification of possible strength imbalances in elite soccer goalkeepers, which should be further reduced during the preparatory period. Screening examination of strength asymmetry may be thus a useful tool for both performance and injury prevention in goalkeepers.